72: Accuracy Testing of Transcutaneous Jaundice Meters: Should Transcutaneous Jaundice Meters be Used Right Out of the Box?. Issue 6 (1st June 2014) - Baerg, K; Smith-Fehr, J; Irwin, H; Lyon, M
Abstract: BACKGROUND: Screening total serum (TSB) or transcutaneous (TcB) bilirubin in all infants is recommended. The JM-103 Drager Jaundice meter is approved for TcB screening in Canada. OBJECTIVES: The accuracy of six TcB meters was determined by comparing meter results with the clinical laboratory TSB results. DESIGN/METHODS: Ethical approval was obtained for this prospective observational study. Participants received the institutional standard (TSB) for bilirubin screening. Infants under 14 days of age, over 35 weeks gestation, with no history of phototherapy or transfusion were eligible. Prior to TSB collection, skin tone and sternal TcB readings were obtained. Enrolment continued until there were at least five participants, for each of six meters in each TSB range (TSB <150 μmol/L, 151 μmol/L to 250 μmol/L, and >251 μmol/L). Up to five TcB meter readings were obtained per participant. Data was analyzed using Deming regression to determine the relationship between TcB and TSB for each meter. Regression slopes for each meter were compared for statistical significance (P<0.05). RESULTS: Two hundred and four participants were enrolled in this study and 909 TcB meter results were obtained. The regression line for each meter is the following, Meter 1: y = 1.05x − 6.8; Meter 2: y = 0.94x − 11.4; Meter 3: y = 0.96x − 14.3; Meter 4: y = 0.88x − 10.5; Meter 5: y = 0.97x − 20.6; Meter 6: y = 0.89x − 4.3. The regression slope for Meter 1 was significantly different from meters 2–6. The regression slopes for meters 2–6 were not significantly different. At TSB = 100 umol/L, Meters 2–6 results ranged from 76 μmol/L to 81 μmol/L while Meter 1 reported 94 μmol/L. At TSB = 200 μmol/L, Meters 2–6 results ranged from 167 μmol/L to 178 μmol/L and Meter 1 reported 200 μmol/L. At TSB = μmol/L, Meters 2–6 results ranged from 304 μmol/L to 326 μmol/L while Meter 1 reported 359 μmol/L. Significantly different TcB results were obtained with meter 1 when compared with meters 2–6 results. Results obtained with meters 2–6 were not significantly different. No mathematical adjustment to an intervention nomogram can accommodate TcB readings from both Meter 1 and Meters 2–6. CONCLUSIONS: Correlation of new meters with the clinical laboratory TSB method is required to determine specific action thresholds before integration of meters into community screening protocols. Our study demonstrates that TcB meters may report clinically significant variant results. Furthermore, between-meter accuracy must be determined before different TcB meters are used for longitudinal clinical surveillance (trending).